Cardiovascular disease and its foetomaternal outcome in pregnant women undergoing delivery in a tertiary care teaching hospital - Shrestha, Roshan; Raj Regmi, Shyam; Mani Dhital, Bishnu; Hussain, Asraf; Gurung, Puran; Shrestha, Suresh; Sapkota, Sanjiv; Panta, Aiuska (Journal of Chitwan Medical College, 2026)
Introduction: Cardiovascular disease (CVD) in pregnancy poses significant risks to mother and foetus. This study aimed to describe the spectrum of CVD and maternal and foetal outcomes in a hospital setting in Nepal. Methods: A retrospective, cross-sectional study was conducted using hospital records at the Department of Obstetrics and Gynaecology at Chitwan Medical College Teaching Hospital (CMCTH). Pregnant women with CVD admitted beyond 22 weeks of gestation for delivery from Nov 2019 to Dec 2024 were enrolled. Ethical approval was obtained. Maternal outcomes included mode of delivery, cardiac care unit (CCU) admission, and mortality. Foetal outcomes included gestational age, birth weight, intrauterine growth restriction (IUGR), stillbirth, neonatal ICU admission, and early neonatal death (NND). Data were analysed using SPSS version 25. Categorical data are presented as frequency (percentage). Results: Among 191 patients who delivered at CMCTH, hypertensive disorders of pregnancy were most prevalent, seen in 153(80.1%), followed by rheumatic heart disease in 30(15.7%), congenital heart disease in 6(3.1%), and cardiomyopathy in 2(1.0%). The most common maternal outcome was emergency caesarean section in 109(59.1%). Admission to CCU occurred in 30(15.7%), and maternal mortality in 2(1.0%). Foetal adverse outcomes were low birth weight in 80(41.9%), preterm birth in 63(33.0%), and IUGR in 51(26.7%). Stillbirth and early neonatal death each occurred in 6(3.1%). Conclusions: Hypertensive disorders constitute the major burden of CVD in pregnancy at this centre and are associated with high rates of operative delivery and adverse perinatal outcomes, including low birth weight and prematurity.